Shelby American 60 Years of High Performance : The Stories Behind the Cobra, Daytona, Mustang GT350 and GT500, Ford GT40 and More /: The Stories Behind the Cobra, Daytona, Mustang GT350 and GT500, Ford GT40 and More. (2023) - Comer, Colin; Kopec, Richard J
No abstract available